Adsorption of Waste Metal Cr(VI) with Composite Membranes (Chitosan-Silica Rice Husks) - Zulti, Fifia; Dahlan, Kiagus; Sugita, Purwantiningsih (UI Scholars Hub, 2012)
Chromium compounds are widely used in modern industry. Many of these compounds are dumped into the surrounding environment. Membrane technology is more efficient and effective than conventional methods for waste treatment. The research objective was to make a membrane separation process that can be applied to Cr(VI). Membranes were made from chitosan and silica rice husks. Variations of chitosan and silica rice husk used (g) are 2:1 (A1), 2:2 (A2), 3:1 (B1), and 3:2 (B2). The membrane was made by using an inverted phase technique. Results of SEM characterization of membranes showed that B2 has the largest pores at 2.58 μm. The FTIR characterization results indicate the presence of crosslinking between chitosan with silica rice husk with the appearance of Si-O adsorption band at wavelength 1122- 980/cm. A1 membrane, with the smallest pore size has the greatest rejection value towards Cr(VI) which is 70%. The result of this research showed that the composite membrane of silica rice husk was effective enough to adsorb metal Cr(VI) with an average adsorption capacity of 1665.85 mg/g.